Data for: Economia Circular em contextos locais. Caso Equador - Guerrero-Villegas Wilma Matilde (2024)
The concept of the circular economy, characterized as a regenerative and restorative process aimed at enhancing the value of materials through their integration into new production cycles, has been a focal point in academic discourse for over two decades. This research seeks to define the path followed by the Ecuadorian State to incorporate the circular economy definition into ecuadorian legal framework as an element of public policy. Additionally, it is intended to infer if this new conception of the economy is known and applied at the territorial level through the analysis of four territorial development plans of autonomous municipal governments of the northern zone. In the methodology, it was used primary sources through interviews with local government officials, and secondary sources to exhaustively analyze the different milestones about the construction of circular economy legal framework, including Environment and Production Organic Codes and Territorial Development Plans. The findings let to conclude that, although the circular economy is a recent initiative, 2019, the government has been able to issue important public policy guidance documents such as the Libro Blanco and the Circular Economy Organic Law. However, at the territorial level, circular economy conceptions and principles are poorly known or debated by local governments, being solid waste management the greatest compliance pillar related to this new economic trend, although this activity is a competence of the autonomous governments established in the Código de Ordenamiento Territorial and not necessarily because there is an intention to incorporate a circular economy model into development planning.